Improving unsustainable livelihood through marketing interventions: A case on rickshaw pullers. Issue 2 (2014) - ,; ,
Abstract : Purpose – The purpose of this paper is to describe an initiative to improve the daily earnings of a rickshaw puller by training them to retail branded FMCG products based on a "bulk buying retail selling" model. The paper is based on the findings of a survey conducted 112 rickshaw pullers in a semi‐urban district of eastern India. It also dwells on the business of rickshaw pulling and the socio‐economic status of the rickshaw puller. Critical issues related to the sustainability and the future of such interventions on a large scale has also been discussed.Design/methodology/approach – An initial survey of 112 rickshaw pullers was done using a structured schedule that captured data related to age, literacy level, earnings per day, ownership and working hours. Some additional aspects related to socio‐cultural aspects were also collected as an unstructured interview. A secondary survey from 107 respondents representing different sections of the society who frequently use rickshaw as a means for transport was also done to take an opinion on intervention issues.Findings – Findings of the paper suggest that rickshaw pullers have three distinct strategic advantages of literacy, access and mobility, which makes them a potent resource for marketing intervention.Research limitations/implications – The paper reflects on a systematic intervention plan that can change the socio‐economic pattern of rickshaw pulling. A possibility of contributory roles from garage owners and wholesellers is also explored. The proposed scheme may also bail‐out the small‐scale industries and handicraft businesses in villages. Major limitations of the research are long‐term sustainability and large‐scale implementation of the proposed model.Practical implications – The paper can act as a manual for small entrepreneurs and NGOs working in the social‐development area for implementing schemes targeted at rickshaw pullers. The paper also has valuable points for the consideration of policy makers.Originality/value – The research has given insights in to the livelihood aspect of one of the most essential but neglected modes of transport, i.e. rickshaw pulling. The paper has also identified key strengths that rickshaw pulling has, which otherwise is considered purely physical and low‐skilled job.